Інтеграція внутрішньої торгівлі та торговельного підприємництва: виклики та перспективи - Болтянська, Лариса Олексіївна; Лисак, Оксана Іванівна; Boltianska, Larysa; Lysak, Oksana (Запоріжжя : Видавничий дім «Гельветика», 2024)
UA: У статті розглянуто значення внутрішньої торгівлі та торговельного підприємництва для економіки України. Підкреслюється їхня роль у підтримці місцевих виробників та адаптації до сучасних економічних викликів, включаючи пандемію та воєнні дії. Проведені дослідження динаміки товарообороту внутрішньої торгівлі України, проаналізовані тенденції скорочення кількості суб’єктів торговельної діяльності. Охарактеризовано та проведено аналіз сучасних інструментів сучасної торгівлі, зокрема наведені приклади використання цифрових технологій та інновацій, визначені фактори впливу на споживчий попит населення. /// EN: The article examines the importance of domestic trade and commercial entrepreneurship for the economy of Ukraine. Their role in ensuring economic stability, developing entrepreneurship, supporting local producers, and adapting to modern economic challenges, including the pandemic and hostilities, is emphasized. Domestic trade ensures the circulation of goods between regions, promotes infrastructure development, and creates competition, which leads to an increase in the quality of goods and services and a decrease in prices. In the face of challenges, in particular the COVID-19 pandemic and war, this area of the economy demonstrates its importance in ensuring the country’s self-sufficiency, supporting local producers, and meeting the needs of the population. Commercial entrepreneurship, as a specific type of activity focused on making a profit through commodity and monetary transactions, acts as a driving force for innovation, job creation, and the development of the domestic market. In modern conditions, trends toward digitalization and the introduction of technologies, in particular CRM systems, warehouse automation, and e-commerce, are important. Important tools of modern trade are innovations that increase the efficiency of trading enterprises and ensure the availability of services. Economic challenges, in particular inflation and unemployment, require entrepreneurs to be flexible in doing business. The impact of the war on the Ukrainian economy has led to a decrease in the number of business entities and trade volumes, but the market shows the potential for recovery due to the growth of trade. The relationship between domestic trade and entrepreneurship is a common lever of the competitive environment, market adaptation to changes in demand and promotion of innovative growth.
Integration of domestic trade and trade entrepreneurship: challenges and prospects
Keywords: внутрішня торгівля; підприємництво; торговельне підприємництво; роздрібна торгівля; оптова торгівля; споживчий попит; торговельна інфраструктура; цифровізація; технологічні інновації; електронна комерція; domestic trade; entrepreneurship; trade entrepreneurship; retail trade; wholesale trade; consumer demand; trade infrastructure; digitalization; technological innovations; e-commerce